PET and SPECT Imaging of Tumor Biology: New Approaches Towards Oncology Drug Discovery and Development - Van Dort, Marcian E.; Rehemtulla, Alnawaz; Ross, Brian D. (Current Computer - Aided Drug Design, 2008)
Spiraling drug developmental costs and lengthy time-to-market introduction are two critical challenges facing the pharmaceutical industry. The clinical trials success rate for oncology drugs is reported to be 5% as compared to other therapeutic categories (11%) with most failures often encountered late in the clinical development process. PET and SPECT nuclear imaging technologies could play an important role in facilitating the drug development process improving the speed, efficiency and cost of drug development. This review will focus on recent studies of PET and SPECT radioligands in oncology and their application in the investigation of tumor biology. The use of clinically-validated radioligands as imaging-based biomarkers in oncology could significantly impact new cancer therapeutic development.
Keywords: drug development